2021
DOI: 10.1016/j.jsxm.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Labia Minora Surgery in the Adolescent Population: A Cross-Sectional Satisfaction Study

Abstract: Background Labia minora surgeries are gaining popularity and we have limited data available to help counseling patients, especially in the adolescent population. Aim This study is meant to assess the complications and satisfaction of patients who had the surgery as adolescent. Methods We identified and reviewed all labia minora surgeries performed to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…32 However, it has barely been evaluated in the context of women considering cosmetic surgery. 24 This is of interest as interventions, such as counselling concerned patients or health education in this area, could be measured with this scoring system. We have found that items 1, 2 and 6 are the most affected in women concerned about their genitals and interventions targeting these areas would probably be the most effective when trying to improve women's self-perception.…”
Section: Comparison To Prior Literature and Clinical Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, it has barely been evaluated in the context of women considering cosmetic surgery. 24 This is of interest as interventions, such as counselling concerned patients or health education in this area, could be measured with this scoring system. We have found that items 1, 2 and 6 are the most affected in women concerned about their genitals and interventions targeting these areas would probably be the most effective when trying to improve women's self-perception.…”
Section: Comparison To Prior Literature and Clinical Applicabilitymentioning
confidence: 99%
“…However, FGSIS has been tested in some contexts such as sexual satisfaction, 23 but barely in others such as women's desire of undergoing cosmetic surgery. 24 Although there are scales in Spanish designed to evaluate selfesteem or self-image perception, none of them examine female self-perception about their genitalia (including FGSIS). Therefore, the scale needs validation prior to its use in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 study reported a high complication rate (20.5%) of labioplasty in an adolescent population ( n = 17), with a 6.8% reoperation rate. Nearly half of this sample (47%) reported their labia had changed in size since the post‐operative period 11 …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Nearly half of this sample (47%) reported their labia had changed in size since the post-operative period. 11 It is evident in the literature that concerns about appearance are a key reason given for adult women seeking genital cosmetic surgery. [12][13][14] It has been hypothesised that exposure to social media, web content and pornography might be a driver of FGCS.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Despite poor follow-up and high complication rates, the providers reported that 47% of the participants were fully and 53% partially satisfied with the outcome of the procedure. Also of note, 75% of participants met the cut-off criteria for “Hypoactive Sexual Desire Disorder (HSDD)” [ 25 ]. The retrospective design, poor response rate, small numbers, and the contested diagnosis of HSDD [ 26 , 27 ] raise questions about the value of this research.…”
Section: Outcomes Of Studies That Include Adolescentsmentioning
confidence: 99%